2023
DOI: 10.3390/s23031598
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Emotion with Biosignals: A Comparison of Classification and Regression Models for Estimating Valence and Arousal Level Using Wearable Sensors

Abstract: This study aims to predict emotions using biosignals collected via wrist-worn sensor and evaluate the performance of different prediction models. Two dimensions of emotions were considered: valence and arousal. The data collected by the sensor were used in conjunction with target values obtained from questionnaires. A variety of classification and regression models were compared, including Long Short-Term Memory (LSTM) models. Additionally, the effects of different normalization methods and the impact of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…The prediction performances of the RF and LSTM models were similar. These results deviate from those of previous studies that indicated better predictive capabilities of LSTM than the RF on time-series data [ 31 ]. However, these results agree with the findings of other investigations that reported comparable predictive performance between these two ML models [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The prediction performances of the RF and LSTM models were similar. These results deviate from those of previous studies that indicated better predictive capabilities of LSTM than the RF on time-series data [ 31 ]. However, these results agree with the findings of other investigations that reported comparable predictive performance between these two ML models [ 32 , 33 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Long short-term memory (LSTM) [ 22 , 23 ] was utilized to identify muscle fatigue state. The number of layers of the LSTM model is set as input layer, hidden layer, and output layer through the query of relevant research literature, and the unit is 100.…”
Section: Methodsmentioning
confidence: 99%
“…At a glance, Valence and Arousal classifications must be performed through two independent binary classification tasks. By combining Valence and Arousal, human emotions (e.g., Angry, Happy, Sad) can be expressed; often, these are visualized using Russell’s circumplex model of emotions 54 .…”
Section: Eeg-based Emotion Recognition Through Information Enhancemen...mentioning
confidence: 99%